Epidemiological and genetic variation analysis of emerging porcine circovirus type 2 in Henan Province, 2023 - Leng, Chaoliang; Song, Jiajing; Wang, Jiabao; Zhai, Hongyue; Ayra-Pardo, Camilo; Cao, Jiajia; Li, Junjie; Zhao, Yingying; Shi, Hongfei; Li, Dandan; Kan, Yunchao; Yao, Lunguang; et al. (Frontiers in Veterinary Science, 2025)
Porcine circovirus type 2 (PCV2) is a highly adaptable pathogen with significant implications for global swine health. In 2023, we investigated the prevalence and genetic variation of PCV2 in Henan Province, China, by analyzing blood and tissue samples from 380 pigs exhibiting clinical symptoms of PCV2 infection, including reproductive disorders and respiratory diseases. PCR analysis was used to detect PCV2, and viral sequences from 13 positive samples were characterized through phylogenetic and mutational analyses. PCV2 was detected in 56.58% (215/380) of samples. Nucleotide homology among newly identified PCV2 strains ranged from 95.14 to 100%, and 91.18–99.89% compared to 36 global reference strains. Phylogenetic analysis of the ORF2 gene encoding the viral capsid protein Cap identified PCV2a, PCV2b, and PCV2d subtypes, with most sequences clustering into three PCV2d subgroups (PCV2d-1, PCV2d-2, and PCV2d-3). Notably, the PCV2a strain HN230707 exhibited significant genetic divergence, forming an independent branch. Mutational analysis of the Cap protein revealed key amino acid substitutions in conformational epitope regions (T60S, R63T, N77D, V80L, L185M, A191K, and I200T), potentially contributing to immune evasion. Additionally, unique mutations in the nuclear localization signal and conformational epitope regions were identified in PCV2d subgroups. The emergence of genetically diverse PCV2 strains, particularly novel PCV2d sub-genotypes, raises concerns regarding their potential to evade vaccine-induced immunity. These findings highlight the importance of continuous molecular surveillance and the need for updated vaccine strategies to mitigate the impact of PCV2 on global swine health.